Perancangan Sistem Pakar Untuk Mendiagnosa Penyakit Pada Kucing Dengan Menggunakan Metode Dempster Shafer Berbasis Web - Fauzan Arrahman; Bagas Setiyaki Wicaksono (CV. Multi Kreasi Media, 2022)
Cats are one of the pets that are favored by most humans, cat diseases are caused by viruses, parasites and bacteria that develop in the cat's body without the cat owner realizing it. The problem that often occurs is the lack of understanding and knowledge of cat owners about disease information and how to handle disease in cats when cats get sick. Therefore, in this study, a website-based expert system was built that was able to diagnose diseases in cats based on the symptoms experienced. This expert system was built using the PHP programming language and MySQL as the database. This expert system provides the results of a disease diagnosis, a definition of the disease and provides treatment or treatment solutions. The method used in this expert system is Dempster Shafer, this method has the ability to provide a high level of accuracy, where this method is able to think like an expert, but by using calculations through symptoms that have a density value, the density value is obtained from interviews with specialist or veterinarian.